Adrenal gland dysfunction and myocardial Tissue Doppler echocardiographic abnormalities in Patients with Beta Thalassemia Major: cross sectional study - Garadah, Taysir Said; Jaradat, Ahmed; Mahdi, Najat; Hassan, Zuhair; Das, Nagla (International Journal of Medicine, 2013)
Background: Adrenal, parathyroid gland and myocardial echocardiographic abnormalities are recognized with variable outcomes in patients with transfusion dependent Beta-Thalassemia major (ß-TM). Aim: In this cross-sectional analytic study in patients with ß-TM, we evaluate the left ventricle systolic and diastolic function using Pulsed Doppler (PD) and Tissue Doppler (DT) echocardiogram with simultaneous measurement of serum level of cortisol and parathyroid hormone. Methods: The study was conducted on patients with ?-TM (n = 99, age 15.92±8.92 years) and compared with an age-matched controls (n = 98 age 15.79±8.94 years). In all participants echocardiographic indices of M mode and PD and TD were performed. Blood samples were withdrawn for measuring the serum cortisol, parathyroid and Ferritin. Correlation between the level of cortisol and ferritin level was evaluated. Results: Patients with ?-TM compared with controls, have significantly thicker LV septal wall index of 0.65± 0.26 vs. 0.44± 0.2190, P<0.001 and LV posterior wall of 0.65 ± 0.235 vs. 0.43 ± 0.214, P< 0.001, with no significant dilation of LV cavity in systole and diastole. The systolic function of LVFE% was normal of 51.95?5.5 vs. 5.0?5.6, p=0.23. Furthermore patients with ?-TM have higher E/A ratio (1.54±0.18 vs. 1.23±0.17, P<0.01) and shorter deceleration time (DT) (170.53±13.3 vs. 210.50±19.20 m sec, P<0.01). The ratio of transmitral E wave velocity to the tissue Doppler E wave at the basal septal mitral annulus (E/Em) was significantly higher in ?-TM group (19.68±2.81 vs. 13.86±1.41, P<0.05). The tissue Doppler systolic wave (Sm) velocity and the early diastolic wave (Em) were significantly lower in ?-TM group compared with controls with Sm, of 4.82±1.2 vs. 6.22±2.1 cm/sec, P<0.05 and (Em) of 3.51±2.7 vs. 4.12±2.5 cm/sec P<0.05, respectively). The tricuspid valve velocity was significantly higher in ?-TM patients compared with controls (2.85±0.56 vs. 1.743±0.47 m/sec, respectively, P<0.01). The prevalence of adrenal insufficiency in patients with ß-TM was 16 %, hypoparathyroidism of 4.5%. There was a weak negative correlation between serum level of cortisol and the serum Ferritin. Conclusion: Patients with ?-thalassemia major had a high prevalence of subclinical adrenal insufficiency of 16%, hypoparathyroidism of 4.5% with weak negative correlation between the low level of cortisol ?160 nmol/L and high serum ferritin. Echocardiographic Pulsed Doppler showed a restrictive LV diastolic pattern suggestive of advanced diastolic dysfunction but preserved left ventricle systolic function.